1978
DOI: 10.1111/j.1365-2125.1978.tb01619.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of chronic drug administration on hepatic enzyme induction and folate metabolism.

Abstract: 1 Patients on prolonged treatment with anticonvulsant and phenothiazine drugs exhibited lower than normal concentrations of folate in serum and erythrocytes, and showed increased urinary FIGLU excretion after histidine loading; urinary excretion of D‐glucaric acid was also increased suggesting induction of the hepatic microsomal enzymes. 2 Folate deficiency by enzyme‐inducing drugs was seen to be determined more by the duration of therapy than by the nature of the drugs. Excretion of FIGLU was increased by 70%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Phenobarbitone, for example, has been shown to cause significant deterioration in the therapeutic response to prednisolone in patients with rheumatoid Hansen et al (1971a,b) Cucinell et al (1965) Bloxham et al (1979) Neuvonen and Penttila (1974; Penttila et al (1974) Padgham andRichens (1974) See text (section 2.4.2) Haque et al (1972); Werk et al (1969) Stjernholm and Katz (1975) Meikle et al (1969) Petereit and Meikle (1977) Southern et al (1969) Larsen et al (1970 Reduced therapeutic or prophylactic efficacy Notelovitz et al (1981) Hempel and Klinger ( Pond and Kretzschmer (1981); Stambaugh et al ( 1977Stambaugh et al ( . 1978 Finelli (1976) Gram et al (1980) Labadarios et al (1978 Hahn (1976) Mezey and Robles (1974) Somogyi et al (1981) Davies et al (1969 Phenytoin may potentiate the anticoagulant effect of warfarin. 2 Evidence is conflicting.…”
Section: Glucocorticoids and Metyraponementioning
confidence: 97%
“…Phenobarbitone, for example, has been shown to cause significant deterioration in the therapeutic response to prednisolone in patients with rheumatoid Hansen et al (1971a,b) Cucinell et al (1965) Bloxham et al (1979) Neuvonen and Penttila (1974; Penttila et al (1974) Padgham andRichens (1974) See text (section 2.4.2) Haque et al (1972); Werk et al (1969) Stjernholm and Katz (1975) Meikle et al (1969) Petereit and Meikle (1977) Southern et al (1969) Larsen et al (1970 Reduced therapeutic or prophylactic efficacy Notelovitz et al (1981) Hempel and Klinger ( Pond and Kretzschmer (1981); Stambaugh et al ( 1977Stambaugh et al ( . 1978 Finelli (1976) Gram et al (1980) Labadarios et al (1978 Hahn (1976) Mezey and Robles (1974) Somogyi et al (1981) Davies et al (1969 Phenytoin may potentiate the anticoagulant effect of warfarin. 2 Evidence is conflicting.…”
Section: Glucocorticoids and Metyraponementioning
confidence: 97%
“…Possible causes of the malabsorption include neurogenic inhibition of the phasic and tonic activity of the small intestine or structural changes of the intestinal mucosa which could be brought about by a number of agents including infection (Chapman et al, 1966), or nutritional deficiencies. Folic acid has frequently been found to be deficient in institution diets; in addition anticonvulsant therapy can reduce serum folic acid levels (Labadarios et al, 1978). There was no evidence of folate deficiency in the subjects resident at St Lawrence's Hospital; however, a number of the Hastings patients developed frank folate and/or vitamin B12 and/or iron deficiency.…”
Section: Discussionmentioning
confidence: 94%
“…Hypotheses have included impaired folate absorption (28), hepatic enzyme induction (29,30), and increased folate catabolism (3 1). More recent studies have suggested that neither folate absorption (32) nor folate catabolism (33) are adversely affected by PHT.…”
Section: Folate Deficiencymentioning
confidence: 99%